USING THE COLASOFT CAPSA NETWORK ANALYZER TO DIAGNOSE, PINPOINT AND DETECT A VIRIETY OF MALICIOUS CYBERATTACKS AND TO IMPROVE THE VULNERABILITIES FOR A SOHO NETWORK: USING THE COLASOFT CAPSA NETWORK ANALYZER TO DIAGNOSE, PINPOINT AND DETECT A VIRIETY OF MALICIOUS CYBERATTACKS AND TO IMPROVE THE VULNERABILITIES FOR A SOHO NETWORK - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper a high-level analyzing for different malicious attacks is made. Thanks to the real-time network analyzer Colasoft Capsa some applications problems and vulnerabilities have been detected and thereby this action ensures a protection for the hosts in the SOHO network. Nowadays it is desirable that many cyber-security professionals and net-work managers to use Colasoft Capsa in order to detect and protect the computer and net-work systems against malicious cyber-attacks.